Public speaking to enhance oral Mandarin proficiency / Goh Ying Soon, Lee Chai Chuen and Ngo Kea Leng - Goh, Ying Soon; Lee, Chai Chuen; Ngo, Kea Leng (Research Management Institute (RMI), 2014)
This paper aims to shed some light on the use of Speaking Contest as an Activity to support the learning of Mandarin among non-native Chinese learners. Speaking Contest as an Activity can be a useful tool to motivate the learning of Mandarin among learners. This study was carried out during a Mandarin speaking competition held at UiTM (Perlis). A self-developed questionnaire was distributed to gain understanding and the views of the participants on the use of Mandarin in the speaking contest as an activity to support the learning of a Chinese language among the non-native Chinese learners. Descriptive and inferential statistics were used to analyze the data. The findings revealed that students agreed that Mandarin speaking competition as an activity was useful to enhance their learning. Thus, activities such as Mandarin speaking contest can be used as creative practices in particular when teaching Mandarin as a foreign language and also for other foreign languages.